Culinary Tourism from a Geographical Perspective - Kowalczyk, Andrzej (Turyzm/Tourism, 2005)
Culinary tourism, one part of the wideranging cultural tourism, is becoming increasingly popular. Culinary tourists not only search for taste experiences but also want to develop their understanding, purchase products and so on. The factors which determine the culinary attractiveness of a region are the originality, variety and traditions of its cooking. Culinary tourism not only gives pleasure to its participants but may be an important factor in local development as well.